2005
DOI: 10.1002/tox.20110
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic potential of Microcystin‐LR and nodularin in vitro in primary cultured rat hepatocytes and in vivo in rat liver

Abstract: Microcystin-LR (MCYST-LR) and nodularin (NOD) are known as tumor promoters in experimental animals and so present potential health threats for humans. Although their hepatotoxic mechanisms have been very well documented, many other effects of these toxins are relatively undescribed, indeed controversial, notably those related to their genotoxicity. In the present investigation, we examined how these toxins could induce DNA damage using a combination of in vitro and in vivo approaches. We first used the (32)P-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
0
45
0
1
Order By: Relevance
“…The results of these assays strongly suggest that moderate to high concentrations of MC-LR are not directly genotoxic (Bouaicha and Maatouk, 2004a;Fessard et al, 2004;Zegura et al, 2003), however, do promote the generation of reactive oxygen species and subsequently lead to oxidative DNA damage and transient DNA strand breaks (Zegura et al, 2003;Maatouk, 2004a, 2004b). Consequently a tumour initiating capacity of MC-LR has been suggested.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The results of these assays strongly suggest that moderate to high concentrations of MC-LR are not directly genotoxic (Bouaicha and Maatouk, 2004a;Fessard et al, 2004;Zegura et al, 2003), however, do promote the generation of reactive oxygen species and subsequently lead to oxidative DNA damage and transient DNA strand breaks (Zegura et al, 2003;Maatouk, 2004a, 2004b). Consequently a tumour initiating capacity of MC-LR has been suggested.…”
Section: Genotoxicitymentioning
confidence: 99%
“…This data was obtained by the Comet assay, which measures DNA strand breaks that constitute primary DNA lesions with relevance for the formation of gene and chromosome mutations [48]. Several mutagenicity studies excluded the hypothesis of MCLR being a mutagen [49,50], which was further supported by the fact that MCLR do not form adducts with DNA that would represent a pre-mutagenic lesion [51]. On the other hand, some authors reported that MCLR-induced DNA damage was a consequence of early apoptosis due to oxidative stress and not a real genotoxic effect [52].…”
Section: Genotoxicitymentioning
confidence: 99%
“…So it may be inferred that some other mutagenic toxins present in the extracts or diŠerent routes of administration might be responsible for the positive results observed in those studies. However, MCLR treatment caused enhanced formation of 8-oxo-7,8-dihydro-2?-deoxyguanosine in a time-and dosedependent manner in vitro in primary cultured hepatocytes and in vivo in rat liver cells that could involve in the formation of hepatic tumors during long-term exposure to this cyanobacterial hepatotoxin (33). In contrast, in our study, under present experimental conditions, MCLR failed to induce mutation in both target genes (lacZ and cII) in liver and lungs of TG mouse.…”
Section: Discussionmentioning
confidence: 96%